Advanced hydrogels based on natural macromolecules: chemical routes to achieve mechanical versatility. (December 2022) - Mortier, C.; Costa, D.C.S.; Oliveira, M.B.; Haugen, H.J.; Lyngstadaas, S.P.; Blaker, J.J.; Mano, J.F.
Abstract: Advances in synthetic routes to chemically modify natural macromolecules such as polysaccharides and proteins have allowed designing functional hydrogels able to tackle current challenges in the biomedical field. Hydrogels are hydrophilic three-dimensional systems able to absorb or retain a large volume of water, prepared from a low percentage of precursor macromolecules. The typical fragile elastic structure of common hydrogel formulations often limits their usage. Three main fabrication strategies involving several compounds or multimodified materials known as double networks, dual-crosslinked networks, and interpenetrating networks have been explored to impart mechanical strength to hydrogels. Widely investigated for synthetic polymers, these approaches allow obtaining added-value hydrogels with a large spectrum of mechanical properties. Advances in the development of such hydrogels with biomacromolecules as main constituent materials have enabled the fabrication of hydrogels with improved key properties for medical use, including biocompatibility, controlled release of active substances and tailored biodegradability, while exploring sustainable sources. This review describes recent advances in the use of proteins, as well as natural and semi-synthetic polymers for the fabrication of hydrogels for biomedical applications. Structures processed via double network, dual-crosslinked, or interpenetrating network strategies are reviewed, and emphasis is given to the type of chemical modifications and reactions, as well as the covalent and non-covalent interactions/bonds involved in those mechanisms. Highlights: Biopolymers and proteins-based hydrogels allowing high-performing systems. Natural macromolecules chemical functionalization improvement. Mechanical versatility achievement through covalent and non-covalent interactions. Classic DN, DC, and IPN as tools for new combinations.